Modern aspects of innovative development of construction companies - Shaposhnikova I.О. (Ways to Improve Construction Efficiency, 2021)
The article is devoted to the analysis of modern aspects of innovative activities of construction companies. The problems of introducing innovations, which construction enterprises are faced with today, have been investigated; the impact of the identified problems on the activities of enterprises in the construction industry is noted; attention is paid to the organization of activities, management methods, search for sources of funding for innovations and assessment of the effectiveness of their implementation. The priorities for the further development of enterprises in the construction industry and the main strategic steps in the implementation of innovations have been determined. Attention is focused on the need to introduce innovations into the activities of the enterprise to ensure stable competitiveness. It is noted that among the methods of effective management of innovations, it is necessary to focus on those that will allow the construction company to improve its competitive position in the market. The advantages of introducing innovations into the activities of construction enterprises are analyzed. The main directions of innovative development in the construction industry and the types of innovations in terms of functional orientation have been determined. It is proposed to develop projects for innovative development of enterprises, taking into account the latest world developments in the construction industry. The necessity of conducting economic assessment and risks when introducing innovations has been substantiated. The specified sources of financing for innovative projects, both state and at the enterprise level. The sources of financing the innovative activity of industrial enterprises for five years, as well as the number of applications for utility models in the direction of "construction" are analyzed. The main methods of organizing the innovative activity of a construction enterprise are considered. The sequence of actions for the implementation of innovative development in the activities of construction enterprises has been determined. The main risk factors that enterprises face when introducing innovations into their activities have been identified. The main principles of the risk management system for the innovative development of the enterprise have been determined, should be aimed at mitigating the impact of risks on the final results of the enterprise.